Determination of the Drucker–Prager parameters of polymers exhibiting pressure-sensitive plastic behaviour by depth-sensing indentation - Seltzer, Rocío (2011)
It is presented in this paper a method to determine the Drucker-Prager parameters of pressure-dependent elastic perfectly-plastic polymeric materials by means of depth sensing indentation. This is achieved via an inverse analysis of the load-displacement data resulting from two tests performed with Berkovich and spherical tips. The well-posedness and the effective range of application of the proposed method are carefully assessed. The method is tested for two elasto-plastic materials with mild initial strain hardening (HDPE and PMMA), and the results are compared to those measured using conventional tensile and compression tests. It is found that the pressure sensitivity indexes are accurately predicted, while the yield stress predictions in tension and compression fall within the non-linear portion of the uniaxial stress-strain curves, i. e. within the region where plastic deformation begins.